Neuroprotective activity of galloylated cyanogenic glucosides and hydrolysable tannins isolated from leaves of Phyllagathis rotundifolia - Tan, Hooi Poay; Wong, Daniel Zin Hua; Ling, Sui Kiong; Chuah, Cheng Hock; Kadir, Habsah Abdul (Elsevier, 2012)
The galloylated cyanogenic glucosides based on prunasin (1–7), gallotannins (8–14), ellagitannins (15–17), ellagic acid derivatives (18, 19) and gallic acid (20) isolated from the leaves of Phyllagathis rotundifolia (Melastomataceae) were investigated for their neuroprotective activity against hydrogen peroxide (H2O2)-induced oxidative damage in NG108-15 hybridoma cell line. Among these compounds, the gallotannins and ellagitannins exhibited remarkable neuroprotective activities against oxidative damage in vitro as compared to galloylated cyanogenic glucosides and ellagic acid derivatives in a dose-dependent manner. They could be explored further as potential natural neuroprotectors in various remedies of neurodegenerative diseases.